2020
DOI: 10.20473/jcmphr.v1i1.20287
|View full text |Cite
|
Sign up to set email alerts
|

Newborns Hearing Screening With Otoacoustic Emissions and Auditory Brainstem Response

Abstract: Hearing loss in newborns is a serious matter, if it is not quickly diagnosed and starts early intervention, a child will experience social, speech, language, cognitive, and academic impairments. There is a method of hearing screening in newborns, which is divided into two types, universal newborn hearing screening, and targeted newborn screening. Both of these methods use OAEs and ABR as objective examination tools. The hearing screening method varies in each country, this difference is based on the test equip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Both BAEPs and otoacoustic emissions are alternative hearing tests for children and are part of several regional screening programs. [16][17][18] In a study conducted in Peru in children aged 0 to 4 years, it was concluded that the sensitivity and specificity of otoacoustic emissions were lower compared to BAEPs. 19 However, the choice between BAEPs and otoacoustic emissions is based on available resources and patient characteristics, so the normal values for each test in the population analyzed should be known.…”
Section: Discussionmentioning
confidence: 99%
“…Both BAEPs and otoacoustic emissions are alternative hearing tests for children and are part of several regional screening programs. [16][17][18] In a study conducted in Peru in children aged 0 to 4 years, it was concluded that the sensitivity and specificity of otoacoustic emissions were lower compared to BAEPs. 19 However, the choice between BAEPs and otoacoustic emissions is based on available resources and patient characteristics, so the normal values for each test in the population analyzed should be known.…”
Section: Discussionmentioning
confidence: 99%
“…Tanto los PEAT como las emisiones otoacústicas son opciones para la evaluación audiológica en niños, las cuales forman parte de la pesquisa de varios programas regionales. [16][17][18] En un estudio realizado en Perú con niños de 0 a 4 años, se concluyó que la sensibilidad y especificidad de las emisiones otoacústicas eran menores en comparación con los PEAT. 19 Sin embargo, la elección de PEAT o emisiones otoacústicas se basa en la disponibilidad de recursos y las características de los pacientes, por lo que se deben conocer los valores normales de cada estudio en la población.…”
Section: Discussionunclassified
“…9,10 FIGURE 2. Hearing screening in Indonesia 9,10 The JCIH program (2019) and the Ministry of Health of the Republic of Indonesia (2019) are universal newborn hearing screening (UNHS). Dr. Kariadi Central General Hospital has implemented UNHS where all newborns did the OAE examinations, both babies at risk and without the risk of hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing impairment in infants and children can be caused by maternal and child factors during prenatal, perinatal and postnatal periods. 2 The most common cause of hearing impairment in newborns is congenital abnormalities, with a prevalence of 4-6 infants out of 1000 live births in developing countries. More than 30% of hearing impairment in the prenatal period is caused by diseases, such as measles, mumps, rubella, meningitis, or ear infections.…”
Section: Introductionmentioning
confidence: 99%